A socioecological model of posttraumatic stress among Australian midwives. (February 2017) - Leinweber, Julia; Creedy, Debra K.; Rowe, Heather; Gamble, Jenny
Abstract: Objective: to develop a comprehensive model of personal, trauma event-related and workplace-related risk factors for posttraumatic stress subsequent to witnessing birth trauma among Australian midwives. Design: a descriptive, cross-sectional design was used. Participants: members of the Australian College of Midwives were invited to complete an online survey. Measurements: the survey included items about witnessing a traumatic birth event and previous experiences of life trauma. Trauma symptoms were assessed with the Posttraumatic Stress Disorder Symptom Scale Self-Report measure. Empathy was assessed with the Interpersonal Reactivity Index. Decision authority and psychological demand in the workplace were measured with the Job Content Questionnaire. Variables that showed a significant univariate association with probable posttraumatic stress disorder were entered into a multivariate logistic regression model. Findings: 601 completed survey responses were analysed. The multivariable model was statistically significant and explained 27.7% (Nagelkerke R square) of the variance in posttraumatic stress symptoms and correctly classified 84.1% of cases. Odds ratios indicated that intention to leave the profession, a peritraumatic reaction of horror, peritraumatic feelings of guilt, and a personal traumatic birth experience were strongly associated with probable Posttraumatic Stress Disorder. Conclusions: risk factors for posttraumatic stress following professional exposure to traumatic birth events among midwives are complex and multi-factorial. Posttraumatic stress may contribute to attrition in midwifery. Trauma-informed care and practice may reduce the incidence of traumatic births and subsequent posttraumatic stress reactions in women and midwives providing care. Highlights: Recalled reactions of horror and feelings of guilt during or shortly after witnessing birth trauma predicted probable posttraumatic stress disorder among midwives. Witnessing birth trauma can reactivate personal traumatic birth experiences among midwives. Posttraumatic stress symptoms were associated with intention to leave the profession and may contribute to attrition in midwifery.